March 2021 Update to the Multidimensional Poverty Measure : What’s New - Nguyen, Minh Cong; Wu, Haoyu; Lakner, Christoph; Schoch, Marta (World Bank, Washington, DC, 2021)
The March 2021 update to the Multidimensional Poverty Measure (MPM) involves changes to the data underlying the multidimensional poverty estimates based on the Global Monitoring Database (GMD). This update reports new estimates for circa 2017, revising the estimates that were first published in October 2020. Some changes reflect the availability of more recent survey data for the economies already part of the GMD. Other changes are due to the addition of 9 new economies to the dataset, the release of new population data and new monetary poverty estimates. Notably, this update accompanies the launch of an online dashboard containing the data and results presented in this document. This includes an online tool that allows users to modify the weights used when aggregating the different indicators in the MPM headcount ratio.